Synthesis and Spectral Characterization of Mn(II) and Co(II) Complexes with Tetradentate Macrocyclic Ligand - Bansal, Usha; Goyal, Samta; Agrawal, Swati (Asian Journal of Chemistry, 2021)
Manganese(II) and cobalt(II) complexes were synthesized with [N4] tetradentate macrocyclic ligand using different metal salts i.e. MnCl2, Mn(NO3)2, CoCl2 and Co(NCS)2. The ligand was prepared by condensation of glyoxal and carbahydrazide. All these were characterized by elemental analysis, molar conductance measurements, magnetic moment, IR, mass, electronic and EPR spectral studies. Elemental analysis indicates that the complexes have composition MLX2 where (X = Cl–, NO3–, NCS–). All the complexes were found to be non-electrolytic in nature so can be formulated as [MLX2]. Infrared spectra of metal complexes suggest that the ligand behaves as tetradentate. On the basis of magnetic moment, electronic and EPR spectral data, all the metal complexes were found to be high spin with octahedral geometry.